Preparation and Properties of Low Dielectric Constant Siloxane/Carbosilane Hybrid Benzocyclobutene Resin Composites - Xian Li (MDPI AG, 2021)
Benzocyclobutene-modified silsesquioxane (BCB-POSS) and divinyl tetramethyl disiloxane-bisbenzocyclobutene (DVS-BCB) prepolymer were introduced into the containing benzocyclobutene (BCB) unit matrix resin P(4-MB-co-1-MP) polymerized from 1-methyl-1-(4-benzocyclobutenyl) silacyclobutane (4-MSCBBCB) and 1-methyl-1-phenylsilacyclobutane (1-MPSCB), respectively. The low dielectric constant (low-k) siloxane/carbosilane hybrid benzocyclobutene resin composites, P(4-MB-co-1-MP)/BCB-POSS and P(4-MB-co-1-MP)/DVS-BCB, were prepared. The curing processes of the composites were assessed via Fourier-transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The effects on dielectric properties and heat resistance of those composites with different proportion of BCB-POSS and DVS-BCB were investigated using an impedance analyzer and thermogravimetric analyzer (TGA), respectively. The thermal curing of composites could be carried out by ring-opening polymerization (ROP) of the BCB four-member rings of BCB-POSS or DVS-BCB and those of P(4-MB-co-1-MP). With increasing the proportion of BCB-POSS to 30%, the 5% weight loss temperature (T5%) of P(4-MB-co-1-MP)/BCB-POSS composites was raised visibly, whereas the dielectric constant (k) was decreased owing to the introduction of nanopores into POSS. For P(4-MB-co-1-MP)/DVS-BCB composites, the T5% and k were slightly raised with increasing the proportion of DVS-BCB. The above results indicated that the BCB-POSS showed advantages over conventional fillers to simultaneously improve thermostability and decrease k.